1978
DOI: 10.1104/pp.62.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Gradient of Growth, Spontaneous Changes in Growth Rate and Response to Auxin of Excised Hypocotyl Segments of Phaseolus aureus

Roger Prat

Abstract: Spontaneous growth was studied in excised mung bean ( Phaseolus aureus Roxb.) hypocotyl segments. Measurements were made with a growth-recording apparatus using displacement transducers on single 5-to 6-millimeter samples excised from the growth zone immediately below the hook.Even for a given zone and under controlled experimental conditions, there are differences in the spontaneous growth of individual explants. Nevertheless, in every case, two phases of endogenous acceleration are found at 15 to 20 minutes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 26 publications
2
9
0
1
Order By: Relevance
“…In this context, Johnsson (1966) nature" recognizable from the strip chart growth records, that temperature shifts had profound effects on the frequency of fluctuations as well as on average growth rates, that manipulation generally reduced growth for a period, with response to and recovery from handling unpredictable, and that short period oscillations (SPO) of 5-25 min were found, sometimes superimposed on long period oscillations (LPO) of 45-120 min. Such oscillations often disappear after excision of the roots or of the upper part of the seedling (Kristie and Jolliffe, 1986) or disappear in excised sections (Cosgrove and Green, 1981), although others have found spontaneous changes or periodic fluctuations in growth ofplant sections (Evans and Schmitt, 1975;Prat, 1978). Kristie and Jolliffe (1986) considered that LPOs found in Helianthus, Raphanus, and Cucumis were probably due to nutational movements of the organ tip.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Johnsson (1966) nature" recognizable from the strip chart growth records, that temperature shifts had profound effects on the frequency of fluctuations as well as on average growth rates, that manipulation generally reduced growth for a period, with response to and recovery from handling unpredictable, and that short period oscillations (SPO) of 5-25 min were found, sometimes superimposed on long period oscillations (LPO) of 45-120 min. Such oscillations often disappear after excision of the roots or of the upper part of the seedling (Kristie and Jolliffe, 1986) or disappear in excised sections (Cosgrove and Green, 1981), although others have found spontaneous changes or periodic fluctuations in growth ofplant sections (Evans and Schmitt, 1975;Prat, 1978). Kristie and Jolliffe (1986) considered that LPOs found in Helianthus, Raphanus, and Cucumis were probably due to nutational movements of the organ tip.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been noticed that auxin-depleted segments from coleoptiles (Cline et al 1974) or hypocotyls (Prat 1978) that were submerged in water showed initially a very low growth rate. After a while the growth rate accelerated considerably, e.g., tenfold after 3.5 h (Vesper and Evans 1979).…”
Section: The Cation Exchanger "Cell Wall" Adulterates Ph Valuesmentioning
confidence: 99%
“…Growth measurettients were made with Philips displacertjcnt transducers used as an auxanometer as previously reported (Prat 1978), but with the following modifications. Columns of 4 to 5 segments (20 mm total length) were tised for segments at b, c, and d levels, while single segments were tised for the a level.…”
Section: Growth Measurementsmentioning
confidence: 99%